The Influence of Determined Tax Load, Tax Planning, and Profitability in Profit Management in The Company Manufacturing The Mining Sector, The Coal Sub Sector Listed on The Indonesia Stock Exchange Year - Hidayat, Imam; Sutria, Pinka Oktaviani (APTISI Transactions on Management (ATM), 2023)
This study aims to analyze the effect of deferred tax expense, planning, and profitability on earnings management. The method used in sampling is using a purposive sampling method. The population in this study is manufacturing companies in the mining sector listed on the Indonesia Stock Exchange (IDX) in 2018-2020. Based on the established criteria, 11 companies have been obtained. This study indicates that the deferred tax expense variable does not affect earnings management; tax planning affects earnings management because profitability affects earnings management. The variables of deferred tax expense, tax planning, and profitability affect earnings management. Profitability has a significant effect on earnings management of manufacturing companies in the Coal Mining sector on the Indonesia Stock Exchange in the 2018-2020 period. Deferred Tax Expenses, Tax Planning, and Profitability simultaneously affect the profit management of manufacturing companies in the Coal sub-sector Mining sector on the Indonesia Stock Exchange in the 2018-2020 period. Deferred Tax Expenses have no significant effect on earnings management in manufacturing companies in the Coal Mining sector on the Indonesia Stock Exchange in 2018-2020. Tax planning significantly affects earnings management for manufacturing companies in the Coal Mining sector on the Indonesia Stock Exchange in the 2018 period 2020.